Praktik penilaian karakter dalam pembelajaran PJOK: studi fenomenologi di sekolah dasar Indonesia - Veny Juniarni Hardi; Sumbara Hambali; Andika Arya Wiguna (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2026)
PJOK provides a strong pedagogical context for fostering student character through movement activities, games, cooperation, rule compliance, and social interaction. However, character assessment in physical education remains challenging because character is abstract, contextual, and requires continuous observation. This study aimed to describe character assessment practices implemented by elementary school PJOK teachers, identify the challenges they encounter, and formulate preliminary elements of a character assessment model suitable for PJOK learning contexts. This research employed a qualitative approach with a phenomenological design. The participants were nine PJOK teachers aged 40-45 years, consisting of seven males and two females, with approximately seven years of teaching experience. The study was conducted over eight months in seven elementary schools in Cimahi, consisting of four public schools coded SN1-SN4 and three private schools coded SW5-SW7. Data were collected through in-depth interviews with teachers, PJOK classroom observations, and learning document analysis, and were analyzed through data condensation, data display, and conclusion drawing and verification. The findings indicate that teachers assessed character through direct observation, simple rubrics or checklists, and informal notes that were not always consistently documented. The main challenges included limited standardized instruments, limited instructional time, administrative workload, and assessment subjectivity. These findings highlight the need for a simple, flexible, behavior-indicator-based character assessment rubric integrated into PJOK learning documents.